A study on Impact of Digital Payment Mode on the Customer Buying Behavior towards Health Insurance policy. - Mrs. Sowmya Hegde and Mr. Naveenkumar K, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In India, the insurance sector is undergoing substantial growth, driven by the wave of digitalization. The integration of digital payment systems has streamlined the process of health insurance policy renewal and new policy purchases for customers. Despite these advancements, challenges persist, encompassing privacy concerns, safety issues, and occasional server disruptions. This study aims to assess the influence of digital payment systems on customer buying behavior concerning health insurance policies. Convenience, reliability, and priority of customer have been identified as key factors shaping buying behavior. A sample of 109 responses from the Mangalore region underwent statistical analysis to derive meaningful insights. The findings indicate a significant impact of digital payment systems on customers' purchasing behavior regarding health insurance policies, highlighting the evolving dynamics in this sector and the need for addressing associated challenges